Bauen und Wohnen in Gemeinschaft / Building and Living in Communities : Ideen, Prozesse, Architektur / Ideas, Processes, Architecture - Becker, Annette; Kienbaum, Laura; Ring, Kristien; Schmal, Peter Cachola (Birkhäuser, 2015)
Housing construction is one of the most fundamental tasks of architecture and urbanism. And many cities are experiencing a strong increase in demand from families with children or for mixed and integrated living. Projects designed for owner-occupation often offer ideal solutions, because owner occupants who are both investors and decision-makers set new standards for quality as well as cost savings.